2006
DOI: 10.1080/15700760500365468
|View full text |Cite
|
Sign up to set email alerts
|

Data Use Leads to Data Valuing: Evaluative Inquiry for School Decision Making

Abstract: Despite growing interest in evaluative inquiry as a trigger for development of organizational learning capacity, there exists a paucity of empirical research in this area. This is particularly the case in the context of schools, where systematic inquiry to support decision making and problem solving is hardly a mainstream activity. The purpose of the present inquiry was to examine the nature and benefits of systematic inquiry in schools and to understand forces that serve to enhance or impede schools propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
4
14
0
1
Order By: Relevance
“…That is, the more an organization experiences successful use of evaluation, the more inclined it would be to engage in such practice. This is consonant with our hypothesis that data use leads to data valuing (Cousins et al., ).…”
Section: Framework For Organizational Evaluation Capacitysupporting
confidence: 92%
See 1 more Smart Citation
“…That is, the more an organization experiences successful use of evaluation, the more inclined it would be to engage in such practice. This is consonant with our hypothesis that data use leads to data valuing (Cousins et al., ).…”
Section: Framework For Organizational Evaluation Capacitysupporting
confidence: 92%
“…Results of our own research have tentatively shown that the successful use of evaluation data in organizations fosters their valuing by members as a powerful force for organizational and program change (Cousins, Goh, & Clark, ). From the perspective of integrating evaluation into organizational culture, “data use leads to data valuing” is a hypothesis worth pursuing.…”
Section: Use and Organizational Evaluation Capacitymentioning
confidence: 81%
“…Hamid's (2008) empirical study claimed that principals should cultivate competent knowledge strategies among teachers to consolidate the knowledge culture in schools and help schools become knowledge centers. Cousins et al (2006) suggested that systematic evaluative inquiry, as a means of collecting data, could provide support for decision making in schools. Moreover, the increasing amount of information that should be ordered and taken into account during decision-making processes necessitates the use of information technologies.…”
Section: A Decision-making Support Methods In Educational Institutionsmentioning
confidence: 99%
“…Several authors have advocated that the use of evaluation findings is an important outcome of ECB efforts (Compton et al, 2001;Cousins, Goh, & Clark, 2006;Cousins, Goh, & Elliot, 2007;Dabelstein, 2003;Mackay, 2002;McDonald et al, 2003, Patton, 2008. For evaluation practice to be sustained, organization members must not only use evaluation findings for decision making and action but also communicate and celebrate the uses of their findings.…”
Section: Use Of Evaluation Findingsmentioning
confidence: 99%